Trade in Services: Note on the Measurement and Quality of Data Sources - Julia Woerz; Olga Pindyuk (FIW - Research Centre International Economics, 2008)
This note gives a comprehensive overview of the currently available international databases on trade in services. Notwithstanding problems in data collection arising from the very wide definition of trade in services (i.e. the four GATS modes in contrast to what is traditionally considered as trade in merchandise goods), we identify a considerable room for improvement of the data situation also with respect to Balance of Payments based data. In this paper we survey IMF, OECD, Eurostat and OENB data at the most detailed sector level. We further give a short descriptive overview of Austria's relative position in service trade flows compared to its major trading partners.
Keywords: F14; F21; 330; export of services; services trade data; services FDI data; Austria